KNOWLEDGE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN IMPLEMENTING THE DEEP LEARNING APPROACH IN PALEMBANG ELEMENTARY SCHOOLS - Ramadhona, Rossa; Padua, Shirley A (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the level of knowledge of Islamic Religious Education (IRE) teachers in implementing the deep learning approach in elementary schools in Palembang, Indonesia. The study focused on a single research variable, namely teacher knowledge, which comprised five dimensions: conceptual understanding, technical competence, curriculum integration skills, pedagogical knowledge, and assessment. A quantitative descriptive survey design was employed. The respondents consisted of 208 elementary IRE teachers in Palembang City. Data were collected using a researcher-developed questionnaire that had undergone expert validation and reliability testing. The data were analyzed using descriptive statistics, particularly mean and standard deviation. The findings indicated that IRE teachers demonstrated a high level of knowledge across all five dimensions. The assessment dimension obtained the highest mean score (M = 3.20), followed by technical competence and pedagogical knowledge (M = 3.17), curriculum integration skills (M = 3.16), and conceptual understanding (M = 3.14). These findings suggest that IRE teachers possess a promising cognitive foundation for implementing deep learning. Nevertheless, professional development remains necessary, particularly in strengthening conceptual clarity, designing student-centered learning activities, aligning assessment with deep learning outcomes, and integrating digital resources in meaningful, ethical, and contextually relevant ways. The study recommends practice-based professional development, school-based mentoring, and collaborative teacher learning communities to support the sustainable implementation of deep learning in elementary IRE.